2006
DOI: 10.1016/j.mrgentox.2006.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Chromium picolinate positively influences the glucose transporter system via affecting cholesterol homeostasis in adipocytes cultured under hyperglycemic diabetic conditions

Abstract: Since trivalent chromium (Cr 3+ ) enhances glucose metabolism, interest in the use of Cr 3+ as a therapy for type 2 diabetes has grown in the mainstream medical community. Moreover, accumulating evidence suggests that Cr 3+ may also benefit cardiovascular disease (CVD) and atypical depression. We have found that cholesterol, a lipid implicated in both CVD and neurodegenerative disorders, also influences cellular glucose uptake. A recent study in our laboratory shows that exposure of 3T3-L1 adipocytes to chromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
56
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 56 publications
8
56
1
Order By: Relevance
“…Similar results were presented by Pattar et al (47), who found that chromium picolinate decreased the content of membrane cholesterol in 3T3-L1 cells. This mechanism was connected with enhanced glucose transport stimulated by insulin and increased the translocation of gLuT4 into the plasma membrane.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were presented by Pattar et al (47), who found that chromium picolinate decreased the content of membrane cholesterol in 3T3-L1 cells. This mechanism was connected with enhanced glucose transport stimulated by insulin and increased the translocation of gLuT4 into the plasma membrane.…”
Section: Discussionsupporting
confidence: 90%
“…Pattar et al (50) found that chromium increased membrane fluidity in mouse 3T3-L1 adipocytes. Evans and Bowman (29) found that the addition of chromium led to an increase in plasma membrane fluidity in rat myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that chromium supplementation affects glucose uptake through augmentation of the fluidity of the plasma membrane (22,29,50). It is postulated that GLUT4 has an increased affinity for areas of the plasma membrane that exhibit greater fluidity, leading to an increased incorporation of GLUT4 into the plasma membrane (53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations